MANFAAT WAKAF TUNAI DALAM PEMBANGUNAN EKONOMI UMMAT - M. Hasan Ubaidillah (El-Qist: Journal of Islamic Economics and Business (JIEB), 2012)
Waqf is part of Islamic economics system development that really potential as one of instrument to empowering economy of Islamic people. waqf can include as jariyah's charitable wichs is the reward never hangs up, although someone who gives waqf passed away. To the effect main investment waqf fund is subject to be optimize asset waqf function as medium to increase life quality and human's resource life. One of kind waqf is cash waqf. Cash waqf as smooth asset. The management cash waqf that professional shall, transparent and gets responsibility. Reliable institutes and criterion pock to bring off cash waqf is Syari's financial institutions . With involve Syariah's financial institution in waqf's management cash, therefore besides productive, waqf will can be invested to various investment type that advantages. Cash waqf constitutes one of sector element voluntary one that strongest deep Islamic. Cash waqf also give model mutual fund via mobilization lents fund tilled immortal through professionalism daring that trust in fund management -the. Forwards, waqf as one of voluntary fund in Islam will can become owner Islam trust, which is most composes fair society.